PENGARUH KONDISI EKONOMI MAKRO DAN KARAKTERISTIK BANK TERHADAP EFISIENSI INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Imam Asngari (Department of Development Economics, Universitas Sriwijaya, 2013)
The purpose of study was to analyze the â€œEffect of Macroeconomic Condition and Bank Charastistics to Efficiency of Islamic Banking in Indonesiaâ€. The main variable studied are economic growth (GGDP), Inflation (INFL), Capital Adequacy Ratio and CAR-Asset Size Ratio (RCSIZE), Financing to deposit Ratio (FDR), Non Performance Financing (NPF), and Operational Efficiency (BOPO) of the Islamic Banking industri. The data used are secondary data from Bank Indonesia (BI) and Biro Pusat Statistik (BPS) on basis Year 2000-2013. The method uses multiple regression analysis by Ordinary Least Squares (OLS) estimation. The finding sowed that the model of operational efficiency (BOPO) the determinan of macroeconomic condition and charastistic of Islamic Banking have real influace with the coefficient of determination is quite high at 69.2 percent. Several independent variable such as economic growth (GGDP), Inflation (INFL), and Non Performance Financing (NPF) has a significant influence on the level of Î±=0.05 on Operational efficiency (BOPO) Islamic Banking Industri. The other independent variables (RCSIZE, FDR) no significant affecting on the efficiency because the t test its each variables probabilityÂ less than 5 percenst.Â Nevertheless, the RCSIZE have relationship the same direction on the movement of BOPO, while FDR had a direction opposite to the BOPO. Keywords: Economic Growth, InflationCapital Adequacy Ratio, CAR Asset Ratio, Financing to Deposit Ratio, Non Performance Financing, Operational Efficiency